The prevalence and types of advance care planning use in patients with advanced cancer: A retrospective single-centre perspective, Australia. (4th March 2023) - Veltre, Arron; Broadbent, Andrew; Sanmugarajah, Jasotha; Marshall, Amy; Hamiduzzaman, Mohammad
Abstract : Objectives: In Australia participation rate in Advance Care Directives is 14%, and research is limited on Advance Care Planning (ACP) invitations and uptake among the patients with advanced cancer (PwAC). This study identifies the prevalence and types of documented ACP discussions in PwAC who died within two or four weeks of receiving chemotherapy. Design: A retrospective audit was conducted. Statistical analysis was calculated in SPSS. Difference in ACP invitation and utilization between three groups [control, <2-weeks, and –4 weeks] was measured by Kruskal–Wallis and Chi-square (or Fisher-Exact) tests. Post-hoc follow-up pair-wise comparisons were performed. Adjusted prevalence ratios were estimated using two logistic regression models. Setting: This study was conducted in XXX Coast University Hospital, Australia. Participants: The records of 339 patients were examined and 320 patients were found eligible. Results: Of the 320 PwAC [male: 55%; median age: 65 years], 227 (71%) received ACP invitation, and among the invited patients, 89% used Acute Resuscitation Plan; 54% used Enduring Power-of-Attorney; and 20% completed Advance Health Directives. From 7.5% [ n  = 24] of the patients who received chemotherapy in their last 2-weeks of life, 42% had not received an ACP invitation, 29% didn't have Acute Resuscitation Plan and only 4% completed Advance Health Directives. There were significant differences among Control, <2-weeks, and 2–4 weeks groups in completing Acute Resuscitation Plan ( P  = 0.003) and Advance Health Directives ( P  = 0.045). A significant difference was also observed between control and <2-weeks groups in number of days since Acute Resuscitation Plan used. Completing an Acute Resuscitation Plan was associated with a lower risk of dying within two-weeks of chemotherapy (OR = 0.246; P  = 0.008). Conclusions: Low rates of ACP invitation and use in PwAC, especially who received chemotherapy in 2-weeks of dying confirm a need for embedding and regularly revisiting ACP framework in cancer care and educating staff, patients, and their family caregivers to increase uptake.